BAGAIMANA KUALITAS PELAYANAN DALAM PENGIRIMAN BARANG DAPAT MENINGKATKAN LOYALITAS PELANGGAN DI CV TIRTA FERTINDO PRATAMA SEMARANG - Eka Rahmawati; Hendrajaya; Syamsul Hadi; Hendrajaya Hendrajaya (Bajang Institute, 2025)
To ascertain if the degree of customer loyalty at CV Tirta Fertindo Pratama Semarang is impacted by the quality of the delivery service, a descriptive qualitative research approach is employed. This study uses data reduction, data delivery, and drawing conclusions to conduct data analysis. According to the study's findings, CV Tirta Fertindo Pratama's delivery service in Semarang only satisfies three of the five criteria for service quality: confidence, responsiveness, and empathy. Service quality is compromised by late delivery, delivery operations, and lack of tracking systems. To overcome these problems, you can use delivery technology, monitor damaged or lost goods, and improve communication with customers